"Everywhere You Go, You See English!": Elderly Women's Perspectives on Globalization and English. Issue 4 (1st October 2016) - Lee, Jamie Shinhee
Abstract : Drawing on in-depth interviews, this article discusses folk notions of globalization and examines perceptual and attitudinal responses offered by educationally underprivileged working-class female senior citizens, arguably the most neglected and marginalized social group in contemporary Korea. The present study stresses the importance of incorporating "vernacular data" (Garrett, 2010) into the discourse on globalization and sheds light on the everyday struggles sociolinguistically ill-equipped elderly women are faced with in an increasingly English-saturated and globalization-conscious Korea. The findings of the study indicate that their support for globalization has a nationalistic undertone, and the connection between English and globalization is unequivocally articulated. The participants in the study overstate the importance and predominance of the English language in Korean consumer culture and note that their inability to understand English is a major disability, limiting their independence, negatively affecting their self-image, and forcing them to occupy a disempowered position in the family.